First Report of Leaf Spot Disease in Angelica dahurica Caused by Phoma bellidis in China. Issue 7 (26th January 2016) - Xu, Haijiao; Cui, Jianchao; Zhou, Rujun; Fu, Junfan; Hao, Ning
Abstract: Angelica dahurica is a perennial herb belonging to the Umbelliferae family that has been used as a valuable traditional Chinese medicine. In August 2013, leaf spot disease in A. dahurica was first observed at the Medicinal Herb Garden in Shenyang Agricultural University, Shenyang, Liaoning, China. Morphological assessment, evaluation of culture characteristics, internal transcribed spacer and beta‐tubulin sequence analysis and pathogenicity identified the causal agent as Phoma bellidis . To our knowledge, this is the first report of leaf spot disease in A. dahurica that was caused by P. bellidis .